2008
DOI: 10.1093/her/cyn006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the worry about sexual outcomes scale for use in STI/HIV prevention interventions for adolescent females

Abstract: This study examined the psychometric properties of a new scale to measure adolescents' worry regarding outcomes of risky sexual behavior (i.e. sexually transmitted infections, including HIV [STI/HIV], and unintended pregnancy). The 10-item worry about sexual outcomes (WASO) scale, resulting in two subscales STI/HIV worry and pregnancy worry, was administered to a sample of 522 African-American female adolescents ranging in age from 14 to 18, residing in the southeast United States and participating in a sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
(28 reference statements)
1
27
0
3
Order By: Relevance
“…Perhaps participants with a college education were exposed to sexual networks with a lower burden of STIs. Alternatively, there could be underlying personal characteristics, such as future orientation, sensation seeking, or worry about sexual outcomes, simultaneously impacting both educational attainment and TGP mediators of STI/HIV risk (Robbins & Bryan, 2004; Sales et al, 2009). Finally, research has shown that increased education leads to increased financial earnings, which enable people to afford better housing, healthier food, better medical care, and health insurance (Freudenberg & Ruglis, 2007; Ross & Wu, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps participants with a college education were exposed to sexual networks with a lower burden of STIs. Alternatively, there could be underlying personal characteristics, such as future orientation, sensation seeking, or worry about sexual outcomes, simultaneously impacting both educational attainment and TGP mediators of STI/HIV risk (Robbins & Bryan, 2004; Sales et al, 2009). Finally, research has shown that increased education leads to increased financial earnings, which enable people to afford better housing, healthier food, better medical care, and health insurance (Freudenberg & Ruglis, 2007; Ross & Wu, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Acerca dos referenciais teóricos que fundamentaram a elaboração dos instrumentos, cinco utilizaram um ou mais referenciais, sendo eles provenientes de modelos de Educação em Saúde, dentre eles, um estudo utilizou a Theory of Reasoned Action, Health Belief Model (17) e, três utilizaram a Empowerment Theory (14,15,17) e um baseou-se na Learning Theory e Family Process Theory (19) .…”
Section: Domínios Acessados Código Do Estudounclassified
“…Os modelos de educação em saúde buscam contribuir na compreensão dos comportamentos dos indivíduos e grupos em relação às respostas entre o problema e ações a serem tomadas, articulando as mudanças no contexto mais amplo tornando-as mais significativas, principalmente em termos de suporte social de apoio (22) . É importante ressaltar que das sete escalas avaliadas, seis tiveram como base outros instrumentos já validados para população adulta, as quais foram readequadas para as adolescentes e validados novamente, tais como: Partner Communication Scale e Sexual Communication Self-Efficacy (17,19) ; 45 item HIV Knowledge e 18 item HIV Knowledge (13,18) ; Rosemberg's 10 item Scale (depressão), Phinney Scale ("atitude de ser negra"), Bentovim Walber Body Attitudes (15) e Female Condom Attitude Scale, Sexual Comfort Scale e Male Condom Attitude Scale (16) .…”
Section: Domínios Acessados Código Do Estudounclassified
“…This scale comprised 7 items and was validated with a sample of African American adolescents in a previous study. 36 Participants were asked how frequently they feared that if they talked about using condoms with a sex partner, the sex partner would ''ignore my request,'' ''threaten to hit me,'' ''threaten to leave me,'' ''swear at me or call me ugly names,'' ''hit, push, or kick me,'' ''leave me,'' and ''go out with other girls.'' Each item required a response based on a 5-point Likert-type scale: 1 (never) to 5 (always).…”
mentioning
confidence: 99%